(3JbQjQGJ dGHf GdedG Ydi HYV GdBjGJs - (3CMeO Hf eMeO Hf Ydj GdMUcaj, GHf GdedG ,J (B1003 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B"(3Gdge dGYde dfG EdG eG YdeJfG, GdMeO ddg GdPi GWdY ef TGA ef CLGH Ydi ObGFb eYGfi cJGHg CeG HYO bO SCdfi ef dGjSJWjY s
(3BNQgG (B:s
(3hLhg GdJgGfi HGdHbGA JdKe hJYR GdGeGfi aQMI jHJSe s
(3Vef eLehY , JQJjHgG (B: (3GdSGOS YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B235 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B133s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG RNGQa s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs